2017
DOI: 10.1002/jor.23792
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for a specialized β3 integrin‐based structure on osteocyte processes in bone mechanosensation

Abstract: Osteocyte processes are an order of magnitude more sensitive to mechanical loading than their cell bodies. The mechanisms underlying this remarkable mechanosensitivity are not clear, but may be related to the infrequent α β integrin sites where the osteocyte cell processes attach to canalicular walls. These sites develop dramatically elevated strains during load-induced fluid flow in the lacunar-canalicular system and were recently shown to be primary sites for osteocyte-like MLO-Y4 cell mechanotransduction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 71 publications
0
42
0
Order By: Relevance
“…Then, the number of disrupted canaliculi (loss of canalicular fluorescence and discontinuously stained canaliculi) over the imaging stack of four images was counted, and the percentage of disrupted canaliculi was calculated. Several previous studies have also used the same method for obtaining the Z‐stack images of osteocyte canaliculi and quantifying the disrupted canaliculi over the imaging stack .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the number of disrupted canaliculi (loss of canalicular fluorescence and discontinuously stained canaliculi) over the imaging stack of four images was counted, and the percentage of disrupted canaliculi was calculated. Several previous studies have also used the same method for obtaining the Z‐stack images of osteocyte canaliculi and quantifying the disrupted canaliculi over the imaging stack .…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have also used the same method for obtaining the Z-stack images of osteocyte canaliculi and quantifying the disrupted canaliculi over the imaging stack. 8,[34][35][36][37] The intracortical resorption space in the accumulation region of linear microcracks was also imaged using a confocal microscope, and the resorption space density (Rs.Dn, ##/mm 2 ) was then quantified. 11,27 Moreover, normal osteocytes (fully occupy lacunae, N.Ot.)…”
Section: Spect/ct Scanningmentioning
confidence: 99%
“…Although the role of osteocytes as key mechanosensors has become well accepted, the mechanisms and molecular mediators that account for their cellular mechanobiology are not completely understood. A series of recent studies by our group has demonstrated that there is a unique mechanosensory complex in osteocytes consisting of pannexin 1 channel (Panx1), purinergic P2X7 receptor (P2X7R), α V β 3 integrin, and T‐type calcium channel Cav3.2‐1 …”
Section: Introductionmentioning
confidence: 99%
“…A series of recent studies by our group has demonstrated that there is a unique mechanosensory complex in osteocytes consisting of pannexin 1 channel (Panx1), purinergic P2X7 receptor (P2X7R), ␣ V ␤ 3 integrin, and T-type calcium channel Cav3.2-1. [6][7][8] Panx1, one of the key components of this complex, is a member of the gap junction family of proteins that forms large nonjunctional channels that allow diffusion of ions and small molecules (<1 kDa) between the cytosol and extracellular space. Besides being activated by P2X7R and other purinergic P2 receptors, Panx1 channels are sensitive to voltage, high extracellular K + , and mechanical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue begins with several outstanding reviews that provide updates on the significance of mechanobiology in musculoskeletal research involving cartilage, tendon, muscle and bone, [1][2][3][4][5][6][7][8][9][10] and that span topics from the role of candidate mechanosensors and chemical mediators, 1,5,9,10 in vitro and in vivo models of tissue injury and repair, 3,4 and supporting technologies. 6,7 The majority of original articles following the review papers are related to the mechanobiology of bone and cartilage, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] tissues whose physical regulation have traditionally garnered intensive research focus, followed by complementary research papers in areas of growing prominence: Ligaments, intervertebral discs, and stem cells. [24][25][26][27][28] From this Special Issue in Musculoskeletal Mechanobiology, it is clear that it has become technically possible to trace the impact of mechanics from individual molecules to an entire organism.…”
mentioning
confidence: 99%